WAWASAN AL-QU’RAN TENTANG MUTMAINNAH - Abdul Kallang (fakultas Ushuluddin dan Dakwah IAIN Bone, 2019)
AbstractThe concept of mutmainnah is the serenity that continues through dhikrullahwhich is accompanied by knowledge and awareness of the majesty of AllahAlmighty. The heart of a believer will always be calm and serene under anycircumstances, that is, when he is struck by calamity he is patient, and whenhe receives mercy or pleasure he is not arrogant in competing to give thanksto Allah SWTKeywords : mutmainnah, dhikrullah, patient.Abstrak